PENGARUH TERAPI RELAKSASI BENSON TERHADAP KECEMASAN PADA LANSIA WANITA DENGAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS PAKIS - Amallia, Finata (Jurnal Ilmu Keperawatan Komunitas, 2025)
Background: Aging in a person has been recognized as a universal truth and biologically programmed by hormonal mediation. Old age is often highlighted with multidegradation from various aspects, both physically, phychologically, and socially. The inability of the elderly to adapt to these changes can trigger new problems that will hinder the achievement of elderly well-being such as anxiety, especially women with hypertension. Nonpharmacological management that can be done is Benson relaxation Therapy by prioritizing 4 basic components, namely a calm atmosphere, mental devices, passive attitudes, comfortable positions. Objective: This study aims to determine the effect of giving Benson Relaxation Therapy on anxiety in elderly eomen with hypertension. Methods: This Study used a pre-experimental method with one group pre-test post-test design. The sampling technique used was purposive sampling with a 32 respondents according to predetermined restriction criteria. Data normality test using Shapiro-Wilk Test and hypothesis testing using Paired T-Test. Result: The result of data analysis of respondent characteristhics have obtained the dominance of age in this study is age 60-74 years (68,7%), female gender (100%), the dominance of elementary school education (62,5%), and the most occupations are farmers (90,6%). The results of statistical test using Paired T-Test showed that the significance value was 0,000 ((p) <0,05). Conclusion: This study showed the results that there was an effect of Benson Relaxation Therapy on anxiety in elderly women with hypertension in the Pakis Health Center working area.